Recent Advances in Technology Research and Education Proceedings of the 17th International Conference on Global Research and Education Inter-Academia - 2018 - Laukaitis, Giedrius (Lecture Notes in Networks and Systems,, 2019)
This book presents the proceedings of the 17th International Conference on Global Research and Education, Inter-Academia 2018 held in Kaunas, Lithuania on 24-27 September 2018. The main goal of the conference was to provide an international forum to review, stimulate, and understand the recent trends in both fundamental and applied research. In addition to increasing interest in recent research findings, the conference aimed to strengthen the cooperation between the partners of the Inter-Academia community towards new theoretical and practical research advances. The papers included cover topics in the fields of material science and technology, nanotechnology, plasma physics, biotechnology and environmental engineering, electric and electronic engineering, robotics, measurement, identification, and control, soft computing techniques and modeling, multimedia and e-Learning. The book is a valuable scientific reference resource for the global scientific community.